PENGARUH PENGAWASAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. CITRA RIAU SARANA DUA BAGIAN SORTASI KABUPATEN KUANTAN SINGINGI - Lestari, Sindy Dwi Kurnia; ", Suryalena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The study uses 3 variables which are supervision, work environment and employee performance. In supervision variables have 4 dimensions of standard work, supervision activities to request work result, comparison of job implementation and taking corrective action. In variables work environment have 2 dimensions which are physical work environment and non physical work environment. In variables employee performance have 4 dimensions which are work quallity, employee knowladge, ability and cooperation.As for the population in this study are employees of the sorting section PT. Citra Riau Sarana Dua Kabupaten Kuantan Singingi which amounted to 42 people and the population in this study used as sample by using census method to all employees, the analisis used in this research is the Validity Test, Realibility Test, Simple Linearregression, Multiple Linear Regression, Determination Test (R2),Individual Significant Test ( t Tes), and Significant Test (F test).The result of research show that the implementation of supervision and work environment has a significant effect on employee performance on PT. Citra Riau Sarana Dua Kabupten Kuantan Singingi. The result can be obtained from the questionnaire that is in though and tested with statistic through the SPSS program.Keywords: Supervision, Work Environment, Employee Performance